The Influence of Job Characteristics and Compensation on Work Motivation and Its Impact on Employee Performance at Perumdam Tirta Mayang Jambi - Bebi Fivanka; M. Zahari; Osrita Hapsara (Dinasti Publisher, 2025)
This study aims to describe job characteristics, compensation, work motivation, and employee performance at PERUMDAM Tirta Mayang Jambi, as well as to analyze the influence of job characteristics and compensation on work motivation and their impact on employee performance. The research employs a quantitative approach using a survey method involving all employees as the population, with the sample determined through proportional stratified random sampling. Primary data were collected through questionnaires measuring variables of job characteristics, compensation, work motivation, and employee performance, while secondary data were obtained from the company’s internal reports. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both the measurement and structural models. The findings indicate that job characteristics have a positive and significant effect on work motivation and employee performance. Compensation also has a positive and significant effect on work motivation and employee performance. Work motivation is proven to be a significant mediating variable in the relationship between job characteristics and employee performance, as well as between compensation and employee performance. These results emphasize that well-designed jobs and a fair, competitive compensation system can enhance motivation, which in turn drives employee performance.